Application of Reverse Osmosis Technology in Processing Clean Water into Drinking Water and PureWater with TDS (Total Dissolved Solid) Indicatorat Pelita Bangsa University - Saputro, Edy; Ardiatma, Dodit; Lestari Zakhasi Al Rusyid, Puti; Aulia Rahayu, Wida; Fajria Isnaini, Afni; Darmawan, Arif (DPPM Universitas Pelita Bangsa, 2024)
This activity aims to improve the quality of clean water to become pure water and drinking water using a reverse osmosis system, namely water filtration processing to neutralize tastes, odors and dangerous substances contained in water. One of the obstacles at Pelita Bangsa University is the use of WTP clean water into pure water and drinking water which can be useful in the campus area, such as water supply in laboratory practices. With the activity of making appropriate technology, namely making a Reverse Osmosis device, it is hoped that it can become an alternative for providing drinking water that is suitable for consumption so that lecturers, staff, employees and students can utilize the pure water and drinking water produced. From the results of the water quality test it can be produced that it is still below the specified threshold limit, namely for pH in the range 6.5 – 8.5, and for temperature, namely air temperature ± 3̊C. From the test results, the TDS value shows that the water that comes out of the output membrane is 0. The TDS value for drinking water is around 20 – 22.